Important Risk Factors of Mortality Among Children Aged 1-59 Months in Rural Areas of Shahroud, Iran: A Community-based Nested Case-Control Study - Chaman, Reza (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: The aim of the study was to evaluate potential risk factors of children mortality between 1-59 months of age. METHODS: This nested case-control study was conducted among children born from June 1999 to March 2009 in rural areas of Shahroud, located in the central region of Iran using health care visit reports and follow-up data available in household health records. RESULTS: Mortality was significantly associated with breastfeeding duration (OR: 0.87, 95% CI: 0.81-0.93), total health care visits (OR: 0.90, 95% CI: 0.83-0.98) and low birth weight (LBW) (OR: 7.38, 95% CI: 1.37-39.67). CONCLUSION: In our study, a longer breastfeeding period and more frequent health care visits were two important protective factors, while LBW was an important risk factor for 1-59 month child mortality. It seems, that complex and multiple factors may be involved in mortality of under 5-year-old children, so combined efforts would be necessary to improve child health indicators.